(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Kerubism is a rare hereditary disorder characterized by bilateral enlargement of the gnathic bones in children, with a tendency to spontaneous remission at puberty. In some cases, it can develop without a family history. Aim: This report presents a case of non-hereditary cherubism affecting the dentition in a 7-year-old patient. Case report: A 7-year-old male patient complained of a bilateral increase in volume on the face in the mandibular body and ramus, which had been developing for 3 years, asymptomatically and with slow growth, with no history of similar cases in the family. Intraorally, the increase in volume extended from the canine to the molar, bilaterally, with anomalies in the teeth involved. Hematological tests were within limits. Panoramic radiography and facial CT revealed multiple multiloculated lesions in the mandibular body and ramus bilaterally. An incisional biopsy was performed under local anesthesia, which revealed the presence of multinucleated giant cells. Based on the clinical, imaging and histopathological findings, the final diagnosis was kerubism. Due to the self-limiting behavior of the pathology, surgical interventions were not necessary and the case will be followed up. Discussion: Although the lesions tend to be symmetrical, here they were more prominent on the right side. The radiographic features were typical of the disease. The lesions can cause malocclusions due to ectopic eruptions, as seen in this case. Despite the hereditary characteristic, there was no family history of the disease. Histological and laboratory analyses are important to rule out other fibro-osseous lesions, but clinical and radiographic aspects are paramount in the diagnosis. Once the bone matures, the lesion tends to regress. However, cosmetic surgery may still be necessary afterwards. Conclusion: The diagnosis of the disease should be based mainly on clinical and imaging findings, since histological analysis is of limited value. Once confirmed, the case should be followed up and surgical interventions postponed if necessary at a later date.